Fiqh Review of the Determination of Eid al-Fitr in the Beliefs of the Satariyah Order of Bukittinggi - Hendri; Wadi, Fajrul; Miswardi; Makdin, Hoirol Anuar bin; Rahmiati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This article examines the method employed by the Tarekat Satri community in Bukittinggi to determine the beginning of Ramadan and Eid al-Fitr. This method diverges from the Indonesian government’s official approach in 1445 AH. The study aims to provide a deeper analysis of the astronomical basis of the Satri community’s criteria for determining Eid al-Fitr. This research adopts a qualitative design, drawing on both primary and secondary data. Data were collected through interviews and document analysis. The findings reveal that the Satri method exhibits substantial weaknesses from an astronomical standpoint. First, determining the new moon relies heavily on subjective estimates, such as predicting the arrival of Shaʿban 8 by observing the moon's apparent size. Second, the process lacks systematic rigor because it does not utilize standard astronomical instruments to ensure the precision of observational data. These limitations contribute to the discrepancies between the community’s calendar and the Indonesian government’s official calculations.